STRATEGI CONVERSATIONAL MARKETING PREPP STUDIO DALAM MEMBANGUN ENGAGEMENT DENGAN FOLLOWERS DI INSTAGRAM - Fatimah Amanda Talitha Nabila; Siti Nadya Ulfa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The rapid growth of active social media users in Indonesia is one of the factors for changing the approach to marketing strategy. How marketers attract consumers' attention is an important point, one of which is through conversational marketing to get customer engagement. This study aims to analyze the content of the Matchday on 30 January 2020 to 16 July 2021 on Instagram @preppstudio. This study uses a netnographic method and the data collection is done through online observation. The results of this study are content in the form of videos, images, Instagram Stories, Reels, direct messages, and each feature becomes a support in monitoring and finding interests that can be a way to stay and increase engagement. From the results of the analysis of existing data by connecting the theory used, the formation and improvement of customer engagement with the application of conversational marketing is quite successful.